Single-case report: dynamic changes in cardiac function during shamanic journeying and Qigong meditation - Huels, Emma R.; Carter, Lily; Xu, Gang; Borjigin, Jimo; Harris, Richard E. (Frontiers in Psychology, 2025)
IntroductionPrevious studies have demonstrated acute changes in brain activity that occur during shamanic journeying—an ancient spiritual practice used for physical, psychological, and spiritual healing. However, the effect of shamanic journeying on other physiological measures, such as heart rate variability, remains unknown. We investigated changes in heart rate variability (HRV) during sessions of shamanic journeying (n = 14) in a single subject, as well as during Qigong meditation (n = 8) in the same individual as a positive control.MethodsElectrocardiogram (ECG) signals were recorded and compared between various events during the shamanic journeys (e.g., rest, drumming, shapeshift, post-shapeshift), as well as during periods of rest and Qigong meditation. ECG signals were first visualized using the Electrocardiomatrix (ECM) software and further quantified using the following HRV measures: beats per minute (BPM), average RR interval (AVRR), standard deviation of RR interval (SDRR), root mean square of successive RR interval differences (RMSSD), and the percentage of successive RR intervals that differ by more than 50 milliseconds (pNN50). Segments > 65 s were evaluated for frequency measures, including the absolute power of the low (LF: 0.04–0.15 Hz) and high (HF: 0.15–0.4 Hz) frequency bands and the ratio of LF to HF power (LF/HF ratio).ResultsThe start of shamanic drumming decreased BPM and increased AVRR (compared to rest), as well as increased SDRR, RMSSD, pNN50, LF power, and LF/HF ratio. Upon shapeshifting, BPM, SDRR, and RMSSD all increased and AVRR decreased. BPM remained elevated (and AVRR remained decreased) during the first post-shapeshift period, while the LF/HF ratio decreased. The LF/HF ratio decreased further in the second post-shapeshift period, while HF power and pNN50 were increased compared to drumming initiation. Qigong meditation also increased SDRR, RMSSD, pNN50, LF power, HF power, and the LF/HF ratio compared to rest. Changes in SDRR, LF power, and LF/HF ratio during Qigong meditation were greater than those induced by drumming initiation, while changes in BPM and AVRR were greater during drumming initiation.DiscussionThese data suggest that shamanic journeying involves dynamic, widespread changes in cardiac function and physiology that can be tracked visually in the ECM and captured by ultra-short-term HRV.